Macrozoobenthos Communities Found In The Waters Of Mariah Bandar Springs - Sinambela, Masdiana; Asiati Napitupulu, Martina; Sinaga, Tonggo (International Journal of Science, Technology & Management, 2024)
Macrozoobenthos found in the waters of Mariah Bandar Springs, Pematang Bandar District, Simalungun Regency, along with physical and chemical parameters, where biological samples, namely macrozoobenthos, were taken using a quadrant and physical and chemical parameters of the water were taken using a dark colored sample bottle and then analyzed at the BTKL The waters that originate from the Mariah Bandar spring have very clear and shallow water, so that the bottom of the waters (substrate) can be seen directly, which consists of sandy rocks. The macrozoobenthos community in the waters of Mariah Bandar spring consists of four classes, namely Clitellata, Gastropod, Bivalvia, Insecta, and eight families, namely Lumbricidae, Thiaridae, Cyrenidae, Chironomidae, Gomphidae, Paludicola, Coenagrionidae, Libellulidae. The temperature at each observation station ranges from 220C – 350C, brightness ranges from 4 – 4.5 m from the surface, dissolved oxygen (DO) ranges from 6.84-8.25 mg/l, pH ranges from 7.36-8.85 , BOD ranged from 1.01-3.42 mg/l. In general, the physical and chemical parameters measured still support the life of freshwater organisms, unless the pH is classified as acid.